134Trends and projections of Treatment as Prevention strategy in Africa and progress towards UNAIDS targets. (2nd September 2021) - Nguyen, Phuong; Le, Phuong; Onishi, Kazunari; Nguyen, Huy; Gilmour, Stuart
Abstract: Background: Africa is lagging behind in progress toward global HIV/AIDS elimination targets. We estimated trends in and projections of annual HIV testing and condom use at last higher-risk sex; and calculated the probability of reaching key UNAIDS's target. Methods: We included 114 nationally-representative datasets in 38 African countries from DHS and MICS with 1456224 sexually active adults age 15-49 from 2003 to 2018. We applied Bayesian mixed effect models to estimate the coverage of annual HIV testing and condom use at last higher-risk sex for every country and year to 2030; and the probability of reaching UNAIDS testing and condom use targets of 95% coverage by 2030. Results: Seven countries saw downward trends in annual HIV testing and four saw decreases in condom use at higher-risk sex, while most countries have upward trends in both indicators. The highest coverages of testing in 2030 are predicted in Swaziland, Uganda and Lesotho. Meanwhile, Swaziland, Lesotho, and Namibia will have the highest proportion of condom use in 2030. The probabilities of reaching targets were very low for both HIV testing (0%-28.5%) and condom use (0%-12.1%). Conclusions: We observed limited progress on annual HIV testing and condom use at last higher-risk sex in Africa, and little prospect of reaching global targets for HIV/AIDS elimination. Key messages: Although some global sponsor agencies are considering withdrawal from supporting Africa, more considerable attention to funding and expanding testing and treatment are needed if HIV/AIDS elimination in Africa is to become more than a distant dream.